The effects of cucurbitacin E on GADD45β‐trigger G2/M arrest and JNK‐independent pathway in brain cancer cells - Cheng, An‐Chin (J Cell Mol Med, 2019)
Cucurbitacin E (CuE), an active compound of the cucurbitacin family, possesses a variety of pharmacological functions and chemotherapy potential. Cucurbitacin E exhibits inhibitory effects in several types of cancer; however, its anticancer effects on brain cancer remain obscure and require further interpretation. In this study, efforts were initiated to inspect whether CuE can contribute to anti‐proliferation in human brain malignant glioma GBM 8401 cells and glioblastoma‐astrocytoma U‐87‐MG cells. An MTT assay measured CuE's inhibitory effect on the growth of glioblastomas (GBMs). A flow cytometry approach was used for the assessment of DNA content and cell cycle analysis. DNA damage 45β (GADD45β) gene expression and CDC2/cyclin‐B1 disassociation were investigated by quantitative real‐time PCR and Western blot analysis. Based on our results, CuE showed growth‐inhibiting effects on GBM 8401 and U‐87‐MG cells. Moreover, GADD45β caused the accumulation of CuE‐treated G2/M‐phase cells. The disassociation of the CDC2/cyclin‐B1 complex demonstrated the known effects of CuE against GBM 8401 and U‐87‐MG cancer cells. Additionally, CuE may also exert antitumour activities in established brain cancer cells. In conclusion, CuE inhibited cell proliferation and induced mitosis delay in cancer cells, suggesting its potential applicability as an antitumour agent.